Fuzzy logic–based evaluation of visualizations generated by intelligent decision support systems. (January 2018) - Ltifi, Hela; Amri, Saber; Ben Ayed, Mounir
The development of intelligent decision support systems requires much research effort to solve decision-making problems' complexity. In fact, the combination of both intelligent components and visualization aspects in intelligent decision support system required a lot of efforts in order to develop advanced information visualization schemes for decision-making processes. For this, an efficient evaluation of these systems has become a major concern for applications in multiple fields. The reports of the existing usability evaluation studies are helpful to verify the potential and the limitations of these tools. However, it is important to integrate more relevant metrics for visual analytics tasks in dynamic intelligent decision support system. The proposed method consists of a questionnaire that is given to the users and a subsequent analysis of the resulting data using fuzzy logic. The advantage of the fuzzy model is its ability to transform the input survey scores into linguistic variables, as well as linguistic evaluation of the overall intelligent decision support system visualization tool. With this approach, it is possible to model the vagueness in the ordinal judgments obtained from the users' evaluation about the visualizations of intelligent decision support system and to support uncertainty in such evaluation.